Dysentry in children under five year of age: a longitudinal prospective study in primary health care in Indonesia - Yati Soenarto; Achmad Suryono; Suharyanto Supardi (Indonesian Pediatric Society, 2001)
We conducted a longitudinal community-based survey between August 1991 and August 1992 started with a pilot study in May 1991 in two rural villages which involved 497 children aged 0-59 monhs, 58 community health workers (CWHs), 44 community representatives, and 5 health center personnel. The qualitative component was carried out using in-depth interviews with the mothers, CWHs, and health personnel. It appeared that the three terms for diarrhea used in thecommunity were similar to medical terminology. However the community perception was that only cases of diarrhea with dehydration should be referred to the health center (HC) for tretment; bloody diarrhea was not considered to be referred. Through case findings, 168 (33.8%) diarrheal episodes were identified among 141 children (1.2 episodes per child). Twenty-two of 168 cases (13.1%) had bloody stool, shigella was isolated in 9 (41%) of these patients. No death occurred in this study. Diagnostic agreement on bloody and watery stool specimens between HC personnel and CHWs was analyzed using data from the 72 stool specimens that were seen by both parties, which showed a kappa coefficient of 0.50. Breast feeding (90%) nand additionalk food (89%) were given during diarrhea in almost all cases. Oral rehydration salts solution was given in 80% odf cases. The study shows that the existing treatment guidelines in the HCs were not properly followed by the health personnel.